Decision making and welfare assessment in canine osteoarthritis - Belshaw, Zoe (2017)
Little has previously been described about how or why owners, veterinary nurses or veterinary surgeons make decisions about pets under their care. The Animal Welfare Act (2006) and the Royal College of Veterinary Surgeons’ oath should ensure the health and welfare of pets in the United Kingdom (UK) is the central focus of those decisions. The aim of this thesis was to characterise the nature and basis of decisions made about the treatment and welfare of osteoarthritic dogs by owners, veterinary surgeons and veterinary nurses. Three studies were performed. Firstly, two rapid reviews identified and appraised the outcome measures used in the peer-reviewed literature to assess canine quality of life and canine osteoarthritis. Secondly, thirty-two interviews were performed with owners of dogs with osteoarthritis and five focus groups were performed with veterinary surgeons and veterinary nurses who manage osteoarthritic dogs. Thematic analysis performed on transcripts of those interviews and focus groups identified key themes. Thirdly, a prospective study was performed to test a novel home monitoring outcome measure for use by owners of osteoarthritic dogs, developed using data gathered in the previous studies.